2013
DOI: 10.1073/pnas.1303380110
|View full text |Cite
|
Sign up to set email alerts
|

MHC class I molecules are preferentially ubiquitinated on endoplasmic reticulum luminal residues during HRD1 ubiquitin E3 ligase-mediated dislocation

Abstract: Misfolded MHC class I heavy chains (MHC I HCs) are targeted for endoplasmic reticulum (ER)-associated degradation (ERAD) by the ubiquitin E3 ligase HRD1, and E2 ubiquitin conjugating enzyme UBE2J1, and represent one of the few known endogenous ERAD substrates. The mechanism by which misfolded proteins are dislocated across the ER membrane into the cytosol is unclear. Here, we investigate the requirements for MHC I ubiquitination and degradation and show that endogenous misfolded MHC I HCs are recognized in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
59
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(62 citation statements)
references
References 29 publications
3
59
0
Order By: Relevance
“…Intriguingly, ubiquitylation of the non-secreted immunoglobulin light chain NS-1, a natural ERAD substrate of the Hrd1 ligase in mammals, occurs on lysine as well as serine and threonine residues, although the E2(s) involved in this process are not known (Shimizu et al, 2010). Moreover, degradation of MHC class I molecules via Hrd1 and UBE2J1, an additional mammalian Ubc6 homologue, and turnover of T-cell Antigen Receptor α-Chain involves the ubiquitylation of non-lysine residues within the substrate (Burr et al, 2013;Yu and Kopito, 1999). Finally, recent studies of the degradation of the yeast E3…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, ubiquitylation of the non-secreted immunoglobulin light chain NS-1, a natural ERAD substrate of the Hrd1 ligase in mammals, occurs on lysine as well as serine and threonine residues, although the E2(s) involved in this process are not known (Shimizu et al, 2010). Moreover, degradation of MHC class I molecules via Hrd1 and UBE2J1, an additional mammalian Ubc6 homologue, and turnover of T-cell Antigen Receptor α-Chain involves the ubiquitylation of non-lysine residues within the substrate (Burr et al, 2013;Yu and Kopito, 1999). Finally, recent studies of the degradation of the yeast E3…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that three E2 ubiquitin-conjugating enzymes function in mammalian ERAD: Ubc6e/UBE2J1, UBE2J2, and UBE2G2 [54]. Ubc6e forms an E2-E3 pair with Hrd1 and is considered the principal E2 in cellular ERAD [54][55][56]. To further clarify the precise mechanism by which Ubc6e is cleaved, we investigated whether EV71-encoded viral proteases 2A pro and 3C pro participate in this process.…”
Section: Ev71 Protease 3c Pro Cleaved Ubc6e At Multiple Sitesmentioning
confidence: 99%
“…Yeast Hrd1p, for example, contains six transmembrane domains [58]. Human HRD1 likely has an identical topology [59] and is involved in degradation of misfolded HLA class I molecules in the absence of US2 and US11 [60,61]. Experiments involving the in vitro reconstitution of retrotranslocation using proteoliposomes and purified Saccharomyces cerevisiae proteins suggest that Hrd1p forms a ubiquitin-gated protein-conducting channel [62,63].…”
Section: Discussionmentioning
confidence: 99%